2022
DOI: 10.2196/38387
|View full text |Cite
|
Sign up to set email alerts
|

Informing mHealth and Web-Based Eating Disorder Interventions: Combining Lived Experience Perspectives With Design Thinking Approaches

Abstract: Background App-based interventions designed to prevent and treat eating disorders have considerable potential to overcome known barriers to treatment seeking. Existing apps have shown efficacy in terms of symptom reduction; however, uptake and retention issues are common. To ensure that apps meet the needs and preferences of those for whom they were designed, it is critical to understand the lived experience of potential users and involve them in the process of design, development, and delivery. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Among the most prevalent barriers reported were concerns regarding technological requirements and data privacy, as well as the accessibility of digital interventions. These results mirror those of prior studies, in which the accessibility, usability and visual design of digital interventions were among the key factors in the decision to engage with services (Jarman et al., 2022). Among the included studies in the current systematic review, the use of digital interventions was associated with significantly less stigma than face‐to‐face therapies.…”
Section: Discussionsupporting
confidence: 87%
“…Among the most prevalent barriers reported were concerns regarding technological requirements and data privacy, as well as the accessibility of digital interventions. These results mirror those of prior studies, in which the accessibility, usability and visual design of digital interventions were among the key factors in the decision to engage with services (Jarman et al., 2022). Among the included studies in the current systematic review, the use of digital interventions was associated with significantly less stigma than face‐to‐face therapies.…”
Section: Discussionsupporting
confidence: 87%
“…Since the publication of this synthesis, two additional studies have been published. Jarman et al (2022) sought feedback from seven young women with self‐identified body image issues or eating disorders on the use of app‐based eating disorder interventions. Key themes emerged around the importance of recognizing symptoms and help‐seeking attitudes, the effectiveness of the content and alignment with full recovery and personal values, social connection and instilling hope, and ensuring apps are accessible and appealing (Jarman et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Jarman et al (2022) sought feedback from seven young women with self‐identified body image issues or eating disorders on the use of app‐based eating disorder interventions. Key themes emerged around the importance of recognizing symptoms and help‐seeking attitudes, the effectiveness of the content and alignment with full recovery and personal values, social connection and instilling hope, and ensuring apps are accessible and appealing (Jarman et al, 2022). Most recently, Papastavrou Brooks et al (2023) co‐designed principles to guide research in their lived experience eating disorder clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the present study address the importance of personalisation to meet the adolescents’ individual needs. Personalisation of treatment is viewed positively by individuals with eating disorders [ 70 72 ] and is especially highlighted as important for adolescents [ 73 ].…”
Section: Discussionmentioning
confidence: 99%